2012
DOI: 10.1074/jbc.m112.398180
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Mechanism of HIV-1 Resistance to Rilpivirine

Abstract: Background: Reverse transcriptase mutations E138K and M184I emerged most frequently in HIV-1 patients who failed rilpivirine/emtricitabine/tenofovir combination therapy. Results: M184I reduces polymerase efficiency, and E138K restores it. E138K also reduces rilpivirine binding affinity mainly by increasing its dissociation rate. Conclusion: E138K abrogates the polymerase defect of M184I and increases rilpivirine dissociation. Significance: Our results provide a biochemical explanation for the selection of E138… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
66
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 98 publications
(118 reference statements)
6
66
0
Order By: Relevance
“…The mechanism of E138K-mediated RPV resistance is an increase in the dissociation rate of RPV, which overcomes a smaller enhancement in its rate of association (11). E138K and M184I/V have a mutual compensatory effect in regard to RT processivity and viral replication capacity (9,11,43,44). However, unlike N348I, E138K is relatively rare in treatment-experienced patients (40,(45)(46)(47), despite the fact that it can mutually compensate for M184I/V (43,44).…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…The mechanism of E138K-mediated RPV resistance is an increase in the dissociation rate of RPV, which overcomes a smaller enhancement in its rate of association (11). E138K and M184I/V have a mutual compensatory effect in regard to RT processivity and viral replication capacity (9,11,43,44). However, unlike N348I, E138K is relatively rare in treatment-experienced patients (40,(45)(46)(47), despite the fact that it can mutually compensate for M184I/V (43,44).…”
mentioning
confidence: 93%
“…Although E138K confers modestly reduced susceptibility to ETR and RPV (37)(38)(39)(40), it does not result in reduced susceptibility to EFV and NVP (40)(41)(42). The mechanism of E138K-mediated RPV resistance is an increase in the dissociation rate of RPV, which overcomes a smaller enhancement in its rate of association (11). E138K and M184I/V have a mutual compensatory effect in regard to RT processivity and viral replication capacity (9,11,43,44).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The K d values of rilpivirine, efavirenz, and nevirapine have been reported in the literatures. 31,32) described. 14) Briefly, the heterodimeric HIV-1 RT protein was purified from cell lysates with sequential use of a diethylaminoethyl (DEAE) cellulose column (Whatman), phosphocellulose P11 column (Whatman), Chelating Sepharose Fast Flow (GE Healthcare) charged with nickel sulfate, and RESOURCE S column (GE Healthcare).…”
Section: Preparation Of Hiv-1 Rt Proteinmentioning
confidence: 99%
“…The mechanism of viral resistance to RPV has been studied using transient kinetics approaches (quench-flow and stopped-flow) transient kinetics approaches to determine how subunit-specific mutations in p66 or p51 subunits of HIV-1RT influence association and dissociation of RPV to the NNRIs' binding hydrophobic pocket in RT. They have suggested that E138K mutation in p51 confers reduced susceptibility to RPV in presence and absence of M184V mutation [20].…”
Section: Editorialmentioning
confidence: 99%